Targeted Cancer Therapy Using Engineered Salmonella typhimurium - Zheng, Jin Hai (Chonnam Med J, 2016)
Obligate or facultative anaerobic bacteria such as Bifidobacterium, Clostridium, Salmonella, or Escherichia coli specifically colonize and proliferate inside tumor tissues and inhibit tumor growth. Among them, attenuated Salmonella typhimurium (S. typhimurium) has been widely studied in animal cancer models and Phase I clinical trials in human patients. S. typhimurium genes are easily manipulated; thus diverse attenuated strains of S. typhimurium have been designed and engineered as tumor-targeting therapeutics or drug delivery vehicles that show both an excellent safety profile and therapeutic efficacy in mouse models. An attenuated strain of S. typhimurium, VNP20009, successfully targeted human metastatic melanoma and squamous cell carcinoma in Phase I clinical trials; however, the efficacy requires further refinement. Along with the characteristics of self-targeting, proliferation, and deep tissue penetration, the ease of genetic manipulation allows for the production of more attenuated strains with greater safety profiles and vector systems that deliver designable cargo molecules for cancer diagnosis and/or therapy. Here, we discuss recent progress in the field of Salmonellae-mediated cancer therapy.